Mapping Land Use Land Cover Change in the Lower Mekong Basin From 1997 to 2010 - Spruce, Joseph; Bolten, John; Mohammed, Ibrahim N.; Srinivasan, Raghavan; Lakshmi, Venkat (Frontiers in Environmental Science, 2020)
The Lower Mekong Basin (LMB) is biologically diverse, economically important, and home to over 60 million people. The region has undergone extensive environmental changes due to multiple factors, including agricultural expansion and intensification, deforestation, more river damming, increased urbanization, growing human populations, expansion of industrial forest plantations, plus frequent natural disasters from flooding and drought. The Mekong river is also heavily used for human transportation, fishing, drinking water, and irrigation. To aid water and disaster management, the Mekong River Commission (MRC) uses the Soil & Water Assessment Tool (SWAT) hydrologic modeling framework to help assess impacts of land use land cover (LULC) and other environmental changes on water flow. The LULC map is a primary input to the SWAT framework, and the LULC change can heavily influence the SWAT modeled hydrologic parameters. In an earlier project, the LULC map for LMB SWAT models was updated to 2010 from the previously used 1997 era map from the MRC. The 2010 LULC map applied Landsat and MODIS data, while the 1997 map used Landsat data. For the project reported herein, the LULC change from 1997 to 2010 was mapped for 9 LULC classes and assessed using GIS techniques. The results indicate that permanent agriculture had expanded in certain sub-basins into previously forested areas. Some agriculture was converted to industrial forest plantations. Also changes in forest classes occurred, partially due to shifting cultivation practices and differences in mapping methods for 1997 and 2010. The mapping of deforestation and new permanent agricultural areas aided SWAT modeling of hydrologic runoff and surficial water flow, given permanent agriculture and forests can have different runoff characteristics. The 1997 map under classified some urban areas, which can add uncertainty to the SWAT modeling results, since urban areas tend to show increased runoff relative to most other LULC types. Fortunately, the 2010 LULC map improved identification of urban areas. While more work is needed to further update the LULC map now used in the LMB SWAT models, this assessment provides a baseline on regional LULC impacts that can be used for more robust ecological and hydrological impact assessments.